2011
DOI: 10.1177/0093854811425453
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Offenders’ Criminogenic Cognitions With Status Variables

Abstract: Certain thinking styles promote criminal behavior, and these criminogenic cognitions are not engaged in equally by all offenders. It is imperative to know which offenders are engaging in more criminogenic thinking so their problematic thinking can be targeted and altered during correctional treatment programming. In doing so, correctional mental health professionals may help reduce recidivism. In the current investigation, the researchers sought to identify offenders most likely to engage in criminogenic cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…For example, a recent analysis of criminal thinking styles among a sample of 595 non-IPV adult incarcerated offenders (Mandracchia & Morgan, 2012) found that being single (compared to being in a relationship) was associated with higher levels of controlrelated maladaptive thinking. Although they did not consider offense pathways directly, it is possible to link these types of thinking style with the typologies described above.…”
Section: Cognitive Correlates Of Coercive Controlmentioning
confidence: 99%
“…For example, a recent analysis of criminal thinking styles among a sample of 595 non-IPV adult incarcerated offenders (Mandracchia & Morgan, 2012) found that being single (compared to being in a relationship) was associated with higher levels of controlrelated maladaptive thinking. Although they did not consider offense pathways directly, it is possible to link these types of thinking style with the typologies described above.…”
Section: Cognitive Correlates Of Coercive Controlmentioning
confidence: 99%
“…Among the factors responsible for the growing popularity of criminal thinking in corrections as well as in the criminal justice field overall is its relevance to classifi cation, prediction, and intervention. There is evidence, for in stance, that criminal thinking, in conjunction with certain status (demographic, incarceration, and mental health) variables, can be useful in classifying offenders for both treatment and management purposes (Mandracchia & Morgan, 2012). Moreover, a recent meta-analysis found that general criminal thinking (GCT) success fully predicted recidivism above and beyond the contributions of age and criminal history (Walters, 2012).…”
mentioning
confidence: 99%
“…Age has been predictive of criminal thinking in some studies (Mandracchia & Morgan, 2012;Palmer & Hollin, 2003;Walters, 2003;Walters, Frederick, & Schlauch, 2007) but not in others Walters & Schlauch, 2008). Race also has been used to predict criminal thinking, but produced mixed results.…”
mentioning
confidence: 99%